SMART Rehab: exploring the effects of Strengthening Mental Abilities with Relational Training on Cognitive Functioning for people with Multiple sclerosis - Burge, Rupert (2021)
Background: Multiple Sclerosis (MS) is a progressive neurodegenerative disease that impacts on a range of both proximal and distal outcomes. People with MS commonly experience cognitive problems that have been shown to affect important aspects of life such as employment, mood, and quality of life. Whilst the disease is progressive, and the damage widespread, recovery from damage through neuronal plasticity does occur. There is growing evidence base in cognitive rehabilitation offerings but limited in quality to draw firm recommendations and studies not reporting a clear theoretical underpinning of their interventions hinders development. Training (SMART: Strengthening Mental Abilities with Relational Training) of Derived Relational Responding, a fundamental component of a well-established behavioural theory of cognition – Relational Frame Theory – has been shown to improve cognitive performance as measured by Intelligence Quotient tests. Studies have begun initial applications of relational responding training in cognitive rehabilitation studies.